RAPID value management for the business cost of ownership: readiness, architeture, process, integration, deployment - Wigodsky, Andrew S. (Amsterdam ; Boston : Elsevier, 2004)
The model presented in this manual for the IT professional helps managers work with tech workers and their customers to make a clear and well-substantiated argument for IT service investments. In order to validate and fully explain this model, Wigodsky presents an overview of the "why" behind technology investment for any organization, and combines this with detailed real-world solutions that maximize BCO efficiency. By eliminating the "futz factor" commonly associated with system ownership costs, the book provides a glimpse of the next generation IT architecture, a repeatable process for identifying organization-wide system costs, and a customizable model for integrating BCO management with your people, processes, and technology. Provides detailed technical architectures, processes, and integrated solutions using common computing technologies Helps the reader build a customized model for reviewing the long-term potential costs and benefits of interrelated IT investments Includes observations of HP thought leaders, experienced consultants, and customers on past projects.
Taking a Razor to information technology (IT) -- On the classification of IT components -- Using RAPID to identify relationship between architecture and process -- Readiness: solution strategy -- Architecture: foundation services -- Process: best practice -- Integration: coherent infrastructure -- Deployment: questioning change and decision making -- Business cost of ownership -- Shaping RAPID IT solutions -- RAPID IT components -- Beyond cost of ownership -- Appendix A: Hewlett-Packard ITSM activities -- Appendix B: HP infrastructure operations.
Includes index.
Keywords: Technological innovations -- Management; High technology industries -- Management; New products -- Management; Electronic books